2005
DOI: 10.1127/0941-2948/2005/0088
|View full text |Cite
|
Sign up to set email alerts
|

Missing North Atlantic cyclonic precipitation in ECMWF numerical weather prediction and ERA-40 data detected through the satellite climatology HOAPS II

Abstract: Intense precipitation associated with wintertime North Atlantic cyclones occurs not only in connection with frontal zones but also, and often mainly, embedded in strong cold air outbreaks to the west of mature cold fronts. Coherent structures of cloud clusters organized in mesoscale postfrontal low-pressure systems are frequently found in satellite data. Such postfrontal lows (PFL) can develop into severe weather events within few hours and can even reach Europe causing intense convective rainfall and gale for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…To answer the question we analyzed data from two different precipitation climatologies, namely the Global Precipitation Climatology Project (GPCP) [ Adler et al , 2003] and the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS‐3). Preceding studies for midlatitude cyclones confirm that precipitation structures and intensities in HOAPS‐3 are in good agreement with observations of various precipitation types, including postfrontal lows (PFL) [ Klepp et al , 2005].…”
Section: Analysis Of Satellite Datasupporting
confidence: 62%
“…To answer the question we analyzed data from two different precipitation climatologies, namely the Global Precipitation Climatology Project (GPCP) [ Adler et al , 2003] and the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS‐3). Preceding studies for midlatitude cyclones confirm that precipitation structures and intensities in HOAPS‐3 are in good agreement with observations of various precipitation types, including postfrontal lows (PFL) [ Klepp et al , 2005].…”
Section: Analysis Of Satellite Datasupporting
confidence: 62%
“…Utilizing in situ voluntary observing ship data, it was shown that, in contrast to other satellite products, HOAPS recognizes smallscale intensive precipitation systems in cold air outbreaks with reliable patterns and intensities. This type of precipitation is also mostly missing in a large sample of events investigated in the ECMWF numerical weather prediction and ERA-40 reanalysis datasets (Klepp et al 2005). Furthermore, Klepp et al (2010) demonstrate the ability of HOAPS to detect even light amounts of cold season snowfall with a high accuracy of 96% between point-to-area collocations of ship-based optical disdrometers and satellite data.…”
Section: E Precipitationmentioning
confidence: 95%
“…This is in agreement with previous intercomparison studies that included satellite-based as well as model-based precipitation estimates. These showed regionally large differences among the individual products that are up to 50% in regions of strong precipitation and at high latitudes (e.g., Adler et al 2001;Klepp et al 2005;Beranger et al 2006). Particularly in the tropical regions model-based data (e.g., reanalysis products) are found to perform significantly poorer than satellite-derived fields (Trenberth and Guillemot 1998;Janowiak et al 1998;Shinoda et al 1999).…”
Section: E Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…State‐of‐the‐art satellite retrievals and reanalysis data sets still disagree on global precipitation amounts, patterns, variability and temporal behaviour (Andersson, 2009), with the relative differences increasing in the poleward direction. The estimation of frequency of occurrence and amounts of mixed‐phase precipitation and snowfall is most challenging as results by Klepp et al (2003 and 2005) indicate for North Atlantic cyclones and its post‐frontal precipitation. Hence, satellite based retrievals for the estimation of instantaneous pixel‐level mixed‐phase precipitation need to be ground validated to assess retrieval accuracy across the wide range of synoptic conditions that lead to precipitation.…”
Section: Introductionmentioning
confidence: 99%